Pre-transplantation serum ferritin as a prognostic marker in allogeneic haemopoietic stem cell transplant patients in a tertiary care hospital in Malaysia - Chellappah Thambiah, Subashini; George, Elizabeth; Samsudin, Intan Nureslyna; Hong, Lee Hoong; Chuo, Ling Ling; Ramli, Nabilah; Zakaria, Muhd Zanapiah (Medknow Publications, 2016)
Background: The principal cause of iron overload in patients with haematological malignancies is recurrent red cell transfusions for anaemia. The serum ferritin level reflects the iron burden in the body, in the absence of inflammation or liver disease. In Malaysia, data are lacking on the association between pre-transplant serum ferritin levels and outcome after allogeneic haemopoietic stem cell transplant. Methods: We did a cross-sectional study using retrospective data of 106 post-allogeneic haemopoietic stem cell transplant patients (HLA-matched sibling) with haematological malignancies at Hospital Ampang to determine the relationship between pre-transplant serum ferritin levels and post-transplant outcome, post-transplant complications and survival time. Patients were divided into two groups according to the iron status: serum ferritin level >1000 μg/L (iron overload) and <1000 μg/L. Results: The median age for patients was 30.5 (18-58) years. The median pre-transplantation serum ferritin level and the prevalence of pre-transplantation iron overload were 2423 (408.2-7664) μg/L and 87.5%, respectively. No significant association was found between iron status and demographic factors, type of haematological malignancy and post-transplant complications. Although insignificant, patients with iron overload had a shorter survival time (36 months) compared to those with no iron overload (40 months). There was also no significant association between the iron status and post-transplant outcome. Significant post-transplant complications associated with post-transplant outcome were the need for total parenteral nutrition (TPN) (p=0.014) and chronic graft-versus-host disease (GVHD) (p=0.008). Similarly, significant associations were found between age group (p=0.003), TPN (p=0.035) and chronic GVHD (p=0.012) with survival time using Kaplan-Meir analysis. However, after Cox regression, only age group was found to be significantly associated with survival time (p=0.014). Conclusion: Serum ferritin is an acute phase reactant and its levels increase in the presence of tissue necrosis and inflammation. Both these events occur in haematological malignancies. Although serum ferritin level is a non-invasive, relatively cost-effective, widely available and practical indicator of iron status, it is not specific to iron overload. Therefore, a true association between the serum ferritin level and iron burden is problematic in patients with haematological malignancies.